RESIDUAL METAL CONCENTRATIONS IN ENHANCED COAGULATION WITH FERRIC CHLORIDE AND ALUM FOR TOC REMOVAL - Mohammad Rafiee; Alireza Mesdaghinia; Amir-Hossein Mahvi (European Scientific Journal, ESJ, 2014)
Chemical coagulation with metallic salts has traditionally been used in water treatment for turbidity removal. However, coagulation is also capable of some degree of natural organic matter (NOM) removal, with NOM functioning as a precursor to disinfection by-products (DBPs) formation. Enhanced coagulation is thus introduced to most water utilities treating surface water. Jar-test experiments were conducted to compare the effectiveness of alum and ferric chloride in removing DBPs precursors from eight synthetic water samples, each representing a different element of the USEPA’s 3×3 enhanced coagulation matrix, and the residual metal (aluminum/iron) concentration in the treated water was assessed. Coagulant type influenced the removal of total organic carbon (TOC) and which was enhanced with increasing coagulant dose. For all the treated samples coagulation with ferric chloride proved to be more effective than alum at similar doses and the mean values of treatment efficiencies were 51% and 32%, respectively. Ferric chloride was therefore considered the better chemical for enhancing the coagulation process. The results of residual metal concentration measurements in treated water showed that iron and aluminum concentrations had been increased as expected but the quality of water concerning the residual metal deteriorated much more in cases of under-dosing. Despite expecting high residual Al and Fe concentrations under enhanced coagulation, metal concentrations were frequently remained low and were not increased appreciably.